Meningkatkan Hasil Belajar Pakat melalui Penerapan Model PBL Berbantuan Video pada Materi Ishak Dipersembahkan Kepada Allah Kelas II SD Witama Pekanbaru - Fanny Elvi Novrita Purba; Johanes Subasno; Veronika Sunarningsih (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The main problem in this paper is focused on efforts to improve student learning outcomes in Catholic religious learning activities using the PBL (problem based learning) learning method. Considering that producing a scientific work requires a long process such as exploring ideas, finding references, conducting research or analysis, obstacles and problems are often unavoidable. The aim of problem-based learning was developed to help students develop thinking abilities, develop problem-solving abilities, intellectual skills, and become independent students. The problem-based learning method consists of 8 stages, namely finding problems, defining problems, collecting facts, formulating hypotheses, conducting investigations, refining problems that have been defined, concluding alternative problem solving collaboratively, and testing the results (solutions) of problem solving.